Spatial, environmental, and individual associations with Anopheles albimanus salivary antigen IgG in Haitian children - Jaramillo-Underwood, Alicia; Herman, Camelia; Impoinvil, Daniel; Sutcliff, Alice; Knipes, Alaine; Worrell, Caitlin M.; Fox, LeAnne M.; Desir, Luccene; Fayette, Carl; Javel, Alain; Monestime, Franck; Mace, Kimberly E.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
IgG serology can be utilized to estimate exposure to Anopheline malaria vectors and the Plasmodium species they transmit. A multiplex bead-based assay simultaneously detected IgG to Anopheles albimanus salivary gland extract (SGE) and four Plasmodium falciparum antigens (CSP, LSA-1, PfAMA1, and PfMSP1) in 11,541 children enrolled at 350 schools across Haiti in 2016. Logistic regression estimated odds of an above-median anti-SGE IgG response adjusting for individual- and environmental-level covariates. Spatial analysis detected statistically significant clusters of schools with students having high anti-SGE IgG levels, and spatial interpolation estimated anti-SGE IgG levels in unsampled locations. Boys had 11% (95% CI: 0.81, 0.98) lower odds of high anti-SGE IgG compared to girls, and children seropositive for PfMSP1 had 53% (95% CI: 1.17, 2.00) higher odds compared to PfMSP1 seronegatives. Compared to the lowest elevation, quartiles 2-4 of higher elevation were associated with successively lower odds (0.81, 0.43, and 0.34, respectively) of high anti-SGE IgG. Seven significant clusters of schools were detected in Haiti, while spatially interpolated results provided a comprehensive picture of anti-SGE IgG levels in the study area. Exposure to malaria vectors by IgG serology with SGE is a proxy to approximate vector biting in children and identify risk factors for vector exposure.